THE DEMAND FOR CIGARETTES IN NIGERIA, 1950 - 1971; AN ECONOMETRIC STUDY (1973)
Cigarette, besides being an important source of Excise tax revenue to many countries, has interesting theoretical implications mainly because of the very peculiar consumer needs it satisfies and because it has no exact direct substitute, except substitution among the different brands that exist. Over the years, the consumption of cigarettes in Nigeria has increased remarkably despite all the medical, social and religious campaigns against smoking. This study attempts at explaining the observed variations in the National consumption of cigarettes within the period 1950-71 as influenced by some variables, the strength of which the study tries to measure by applying econometric methods. The variables considered are economic and demographic factors; the economic factors include income and prices while the demographic variable is changes in the proportion of smokers in the population. The study therefore estimates the elasticities of demand for cigarette with respect to income, average price of cigarettes, price index of all other commodities and the demographic factor. The single equation model is adopted to analyse idle annual time- series used in the study. National aggregates as well as per capita data formulations were tested. For the dependent variable (i.e. quantity of cigarettes consumed) aggregation logically means the assumption that cigarettes are homogeneous. The function adopted is non-linear in the original data but linearized in logarithms, the parameters of which were derived by least squares. Besides these other variables, a war-year dummy was introduced in the function to take care of "erractic factors" which affected the consumption of cigarettes during the Nigerian civil-war period, 1967-70. The analysis was carried out on two levels; the static and the dynamic approaches. While in the former the current value of the independent variables influenced the current value of the dependent variable, in the latter, a lagged variable (the quantity variable was lagged) was introduced into the function explicitly. The latter analysis - i.e. the dynamic approach - was applied to test the habit- persistence hypothesis. The results obtained in the study are: (a) the elasticities of demand with respect to income and an average of cigarette prices are low though the income elasticity is comparatively higher. In both cases none was up to 0.7. The price elasticity was particularly low, it was under 0.4. (b) the cross elasticity of demand 'with respect to the price of all other commodities v/as positive and nearer 2 than 1. In other words, it was far greater than unity and thus tends to indicate that consumers were more sensitive to changes in the prices of other commodities than to cigarette prices. (c) 'population', perhaps the changes in the proportion of smokers to non-smokers or the extension of the smoking habit to -the women and members of the lower age group, is a significant factor accounting partly for variations in the National consumption of cigarettes. (d) the habit-persistence hypothesis was supported by the results of this study, that is, the more a person ha3 consumed cigarettes in the past, the more he will consume currently. The estimated "coefficient of adjustment' was about 0.86 which indicates a speedy adjustment of consumption to changes in prices and income. (e) the dummy variable shows positive sign which shows that the National consumption of cigarettes increased during the civil-war despite the temporary loss of the Eastern market. It was suggested from the above result that during major political upheavals the consumption of cigarettes will increase ceteris-paribus. This increase might have been due partly, to the high tension and depressive mood that engulfed the country and, of course, the military consumption. In conclusion, the economic and policy implications of the results were discussed. To the Government, cigarette is one of the products to tax to raise revenue. To the firms engaged in the Tobacco Industry, it might be profitable to pursue a relatively stable retail price policy in view of the high sensitivity of consumers to changes in the prices of other commodities.